COVID-19: Impactos da pandemia e das medidas restritivas na comunidade escolar de Campo Grande - MS - SANDERSON DA SILVA COELHO (2023)
The COVID-19 pandemic caused by SARS-CoV-2 has become one of the great challenges of the 21st century, due to the rapid spread of the virus and high mortality rates. The first outbreak was reported in Wuhan, Hubei Province, China during an alert over multiple cases of pneumonia. Since then, the virus has spread throughout the world and, on May 20, 2020, there were already records of about 4,806,299 people infected with severe acute respiratory syndrome 2 (SARSCoV 2), which caused 319,599 deaths. In Mato Grosso do Sul, the governor of the state, through Decree No. 15391 of March 16, 2020, temporarily suspended all activities that implied the gathering of people and, among them, face-to-face classes in education units. Therefore, the present study aims to identify the psychosocial repercussions of COVID-19 in communities of state and municipal public schools in the city of Campo Grande, Mato Grosso do Sul, evaluating the perception of the school community with respect to the pandemic, restrictive measures and its impacts and investigate adherence to vaccination declared by participants in the studied community. The research had an exploratory nature through descriptive analysis, and tabulation of data in RedCap through the percentage of responses obtained from the questionnaires. As a result, twenty public schools in the city of Campo Grande were accepted, with a total participation of 1,043 individuals, 34.99% of them teachers and 65.0% parents or guardians. The pandemic had major impacts on the return to school period, with 5.3% of students dropping out of school who did not return to school due to the health of a family member or exposure to the virus. Another factor of great impact was the 55.7% reduction in family income that affected 59.63% in eating habits. In addition, a 77.56% prevalence of COVID-19 symptoms was observed in the participants. Having fever, headache, loss of taste, loss of smell, sore throat, nasal secretion and diarrhea the highest rates of symptoms presented. In addition, it was observed in the psychological repercussions of the participants the feeling of fear, anxiety, difficulty in concentration